Investigating the effects of endogenous lipaemia on the measurement of sodium by indirect ion specific electrode potentiometry. (September 2022) - McCarron, Eamon P; Murray, Emma; McKeeman, Gareth C; Coward, Stephen M; Hamilton, Paul; Connolly, Grainne; Roberts, Brona V
Background: The widely automated method using indirect ion specific electrodes (ISE) potentiometry for determination of sodium concentration is prone to interference from lipaemia. Manufacturer-specified lipaemic (L)-index cut offs may underestimate the effects of endogenous lipaemia. Methods: We assessed the interference on sodium concentration caused by endogenous lipaemia in 32 residual samples (from 13 patients) using indirect ISE (Cobas ® 8000 modular analyser with c702 module, Roche diagnostics) and direct ISE (GEM 4000 premier, Werfen) potentiometric methods. Regression analysis (linear and non-linear) was used to determine a reliable (L)-index cut off for reporting sodium concentration. Results: There was a poor correlation observed between triglyceride concentration and (L)-index. There was significant negative interference caused by endogenous lipaemia within analysed samples. Non-linear regression demonstrated a negative interference of approximately 5% at an (L)-index of 250. Conclusion: At present, the manufacturer advises not to report sodium concentration by indirect ISE on the Cobas ® 8000 modular analyser if the (L)-index is >2000. However, this has been determined by the addition of exogenous lipids (Intralipid ® ) and it is clear that this is not comparable to endogenous lipaemia. To ensure patient safety, clinical laboratories should consider lowering the cut off for (L)-index that they use for reporting sodium concentration.